Epilepsy secondary to Menkes' disease: five cases report and review of literature - Pei-yuan ZHANG; Yu-qin ZHANG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
Objective To study the clinical features of patients with Menkes' disease (MD) that initiate from seizures, and to reinforce the knowledge of etiological diagnosis of secondary epilepsy.  Methods The clinical and laboratory features of 5 MD patients who were admitted from December 1992 to March 2014 were retrospectively analyzed.  Results All cases were male infants including two brothers, and the age of onset was 1-5 months after birth. Their clinical manifestations started from tonic (N = 3) and focal clonic (N = 2) seizures. The focal clonic seizures became more frequent and progressively worsened. Four cases showed abnormal background EEG rhythm; 3 cases revealed interictal focal or multifocal epileptiform discharges over occipital region predominantly; 2 cases revealed epileptic discharge in fit period EEG. All the cases manifested severe mental retardation accompanied with light complexion and curly hair. Low serum copper and ceruloplasmin levels were found in 4 cases and lead to the diagnosis of MD. The exceptional one was made clinical diagnosis of MD due to his typical manifestation and the diagnosis of his elder brother. Three cases received MRI examination, which showed extensive cerebral atrophy and symmetric encephalomalacia foci. One case revealed tortuosity of main artery and diminution of distal artery by MRA. One case was treated with phenobarbital, 2 cases with topiramate, one case with topiramate and levetiracetam and clonazepam. One case died of respiratory failure at 24 h after admission. The other 4 cases were followed up for 1-9 months after being discharged, 3 of whom died, and the left one converted to intractable infantile spasms and severe mental retardation, with interictal EEG changing to hypsarrhythmia.  Conclusions The onset of patients with epilepsy secondary to MD often occurs in early infancy, manifesting tonic and focal clonic seizures predominantly with interictal epileptiform discharges over the posterior region in the early stage. Epilepsy secondary to MD shows strong uncontrollability by antiepileptic drugs and poor prognosis.   doi: 10.3969/j.issn.1672-6731.2014.12.010